2019
DOI: 10.1021/acsomega.9b00015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on the Manifestation of the Reaction Selectivity of Nitrogen-Doped Graphene Nanoclusters toward Oxygen Reduction Reaction

Abstract: We investigated the selectivity of N-doped graphene nanoclusters (N-GNCs) toward the oxygen reduction reaction (ORR) using first-principles calculations within the density functional theory. The results show that the maximum electrode potentials ( U Max ) for the four-electron (4e – ) pathway are higher than those for the two-electron (2e – ) pathway at almost all of the reaction sites. Thus, the N-GNCs exhibit high selectivity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Apparently, the codoped systems significantly promote the 2e – pathway. We calculated the equilibrium potential of U = 0.66 V, which is consistent with previous research and further proves that the current theoretical model is appropriate for evaluating the ORR mechanism.…”
Section: Resultssupporting
confidence: 89%
“…Apparently, the codoped systems significantly promote the 2e – pathway. We calculated the equilibrium potential of U = 0.66 V, which is consistent with previous research and further proves that the current theoretical model is appropriate for evaluating the ORR mechanism.…”
Section: Resultssupporting
confidence: 89%
“…37 DFT simulations of the ORR process on catalytic electrodes were performed according to the method based on the computational hydrogen electrode model reported by Nørskov et al 38 Other simulations related to reaction pathways and free-energy diagrams of the ORR process were performed according to a previously reported method. 39 The adiabatic ionization potential was evaluated as the difference in total energy between the neutral and the +1-charged molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Density functional theory (DFT) calculations were carried out using the Gaussian 09 software package with the B3LYP hybrid functional and the 6-311++G­(d,p) basis set for C, N, and H and the cc-pVTZ basis set for Fe, Ni, and Cu . DFT simulations of the ORR process on catalytic electrodes were performed according to the method based on the computational hydrogen electrode model reported by Nørskov et al Other simulations related to reaction pathways and free-energy diagrams of the ORR process were performed according to a previously reported method . The adiabatic ionization potential was evaluated as the difference in total energy between the neutral and the +1-charged molecules.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Insights into the material's edge are found within truncated models, another predominantly relevant physical factor as it has been suggested that the edge graphitic defects have higher ORR activity. 48 Furthermore, a comparison between these two types of modeling approaches indicates the significance of computational periodicity. In this paper, we present a systematic DFT study that includes 12 transition metals with the carbon support containing a graphitic nitrogen defect to provide a foundation in understanding the principal interactions between the metal and support through metal adsorption and the resulting electronic distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical work, such as density functional theory (DFT), can be extremely useful for improving the understanding of N-doped materials. DFT has helped to assist in synthetic variability in determining core-level shifts to elucidate X-ray photoelectron spectroscopy binding energy spectra/experimental signatures. DFT has also been used to directly study the electronic nature of the support and the MSI through defining orbital interactions and band gaps between the metal and support along with calculating relevant MSI metrics, such as adsorption energy of the metal, ripening energy of the metal, and defect formation energies. ,, While these measures can be correlated and extrapolated to physical systems, DFT has also been utilized to explore more macroscopic properties such as predicting affinities for electrochemical absorbates and relative stabilities of nitrogen dopants and their morphologies within the carbon material. , Pyridinic clusters (of three or four pyridinic nitrogen around a vacancy created by missing/defective carbons) have been largely investigated along with graphitic and pyrrolic defects across metals involving Pt, Pd, Fe, Co, and Ni with even inclusions of Ru and Mn. ,, …”
Section: Introductionmentioning
confidence: 99%